Análise estocástica de transitórios em subestações utilizando o método de Monte Carlo integrado ao ATP - Kraulich, Leyla (2016)
This work presents the development of a methodology that uses the resource foreign model , offered by the Electromagnetic Transient Program (ATP-EMTP), in order to realize electromagnetic transient stochastic simulations with emphasis in power substation applications. Due to their stochastic nature, the simulations are performed by employing the Monte Carlo Method to reproduce the randomness and uncertainties that are inherent to the precursory events of some electromagnetic transients. The method is applied in the simulation in order to model the type of study to be analyzed, corresponding to the most frequent and significant transients that are found in substations. These events comprehend: occurrence and clearance of faults, transformer inrush, circuit-breaker switchings and lightning strokes. The suggested methodology allows the use of these resources through the graphical pre-processor software ATPDraw, and it does not need the use of any other external computational tool. Hence, in order to demonstrate the methodology potentialities, this work also presents some examples of applications through ATP-EMTP simulations, employed in a real power system. Throughout this study, it seeks to aid in simulations involving stochastic events in electromagnetic transients by adding new resources to the ATP-EMTP. In addition, this work is a part of a research and development project in a partnership between the Laboratório de Análise e Proteção de Sistemas Elétricos of the Centro de Estudos em Energia e Sistemas de Potência (LAPES-CEESP), located at UFSM, and the Companhia Estadual de Geração e Transmissão de Energia Elétrica (CEEE-GT) of the Rio Grande do Sul state.